Isolasi, Karakterisasi, dan Uji Aktivitas Antioksidan Senyawa Tepenoid dari Kulit Batang Ketapang Kencana (Terminalia muelleri Benth.) - Ranu Muindro, Miranti Verdiana (Chem Info Journal, 2013)
Isolation, characterization, and antioxidant activity test of terpenoid compound from Ketapang kencana Terminalia muelleri bark have been carried out. Isolation was done by extraction, followed by fractionation, and purification. Characterization of chemical structure was conducted using spectrophotometer UV-Vis, FTIR, and GCMS. FTIR spectrum showed characteristic groups of C–O ether aliphatic, CH2, CH3, =C-H, and C=C aromatic. Identification by GCMS resulted that the compound molecular weight was 296 g/mol. The results of antioxidant activity test indicate that isolate from T. muelleri bark does not have a potentiality as antioxidant (IC50= 7424,462 ppm).